Analysis of Attitude Toward Science on Junior High School Students: A Survey Research - Muji Pangesti Prihandini; Nanang Winarno; Eka Cahya Prima; Ratna Ekawati (Didaktika: Jurnal Kependidikan, 2024)
Attitude towards science is one factor that influences student achievement in science learning. Attitude toward science is essential for students, unfortunately, attitude toward science will decrease as the student's grade increases. This research analyzed the attitudes towards Science of Junior High School Students in Indonesia. This research used a survey method. The participants were 1070 junior high school students in Indonesia. The instrument used is a questionnaire and open-ended questions. questionnaire including 40 multiple-choice questions with 4 dimensions. The findings showed the average attitude toward school science (3.18), desire to become a scientist (2.67), the value of science to society (3.60), and perception on scientists (2.89). The average obtained from the four dimensions is (3.08) which means the level of agreement of the student is moderate. Open-ended questions corroborated these results, explaining why students like and do not like science. The three most common reasons students like science are because learning science is fun, studying science will increase knowledge, and often doing experiments. The three most common reasons students don't like science are because science is difficult, has many formulas, and makes them dizzy. The research results show that the average score of students' attitudes toward science is moderate, so teachers are expected to use varied learning models to improve students' attitudes toward science.